Nurses' knowledge towards Intravenous cannula insertion at public and private hospitals in Sana'a City- Yemen - Al- Wesabi, Sadeq Abdo Mohammed; Al- Nahari, Radman Ahmad Ahmad; Al- Khadher, Mugahed Ali Ahmed; Al- Garadi, Abdulfatah Saleh Mohammed (Journal of medical and pharmaceutical sciences, 2021)
Background: the Peripheral IV cannula is one of the most frequently used medical devices in the world; to give intravenous therapy with drugs, and blood components is indispensable in today’s health care.Objective: is to assessing nurses' knowledge towards IV cannula insertion.Methods: Descriptive, hospital- based study, was conducted in Sana'a city in university of science and technology hospital, republican educational hospital, Kuwait educational hospital and Saudi German hospital from June2018 to September 2018, study covered all nurse's in hospital they were (100) nurses, the data were presented in pre- designed questionnaire firstly, then collected by direct interview by participants. Result: The results found a total of nurses have moderate knowledge about IV cannula insertion and indication of insertion (100%), also and about (63.5%) have ability to control in infection before, during and after cannula insertion, the study showed that more than half (71.7%) have good knowledge about site insertion of I.V cannula. Conclusion: The study recommended that regular program to discuss problems that faced them during cannula insertion. Such as lack of general information, not the rehabilitation of nurses scientifically, lack in training courses of nurses and not to evaluate the skills of nurses periodically. Recommendation: The nurses need to be trained, education and conducting courses how to care and maintenance of IV cannula.
Keywords: Intravenous cannula; Knowledge and Practice; Nurses; Sana'a City